Myths and verities in protein folding theories Part II: From Kauzmannâ€™s conjecture to the dominance of the hydrophobic effect - Naim, Arieh Ben (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
Â Â Â We start with Kauzmannâ€™s conjecture regarding the factor which is most likely to determine the stability of the 3D structure of the proteins. We show first that Kauzmannâ€™s model-process, on which the original conjecture was based is inadequate for the process of protein folding. The main reason for this is that protein folding involves the change in the conditional solvation of non-polar groups, not the solvation itself. The â€œconditionâ€ here is the presence of the protein backbone. Secondly, it is argued that various hydrophilic effects, both solvation and interactions are more likely to be dominant both in stabilizing the 3D-structure of proteins, as well as in determining the speed and the specificity of the folding process.